Wanprestasi Perjanjian Kredit Bank Dengan Jaminan (Studi Putusan Nomor 35/Pdt.G/2022/PN Bnj) - Rizki, Rizki; Sembiring, Natan Chalvindo; Simbolon, Gideon Faith; Aisyah, Aisyah (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
here are various factors that can cause a breach of contract (wanprestasi) in a bank credit agreement with collateral, such as economic factors, legal factors, and other factors that influence the execution of the agreement. The research problems examined in this study include how a breach of contract affects an agreement and how the judge's considerations were made in Decision No. 35/Pdt.G/2022/PN Binjai regarding the breach of contract. This study is a normative juridical research, where the data used are secondary data, analyzed and presented using the library research method, allowing for deductive conclusions to be drawn. The conclusion of this study is that the legal considerations used by the judge in Decision No. 35/Pdt.G/2022/PN Binjai reflect the proper and fair application of the prevailing laws and regulations, including provisions on breach of contract, coercive payment (dwangsom), immediate enforceability of the decision, and court costs.